2004
DOI: 10.1590/s0103-84782004000600006
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and path analysis of yield and its components and plant traits in wheat

Abstract: Correlação e análise de trilha de rendimento e seus componentes e caracteres de planta em trigo 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
26
0
10

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 9 publications
7
26
0
10
Order By: Relevance
“…The results of correlation and path analysis are matching for 1000 grain weight, however, the reverse was the case for the other two components where number of grain/spike was the second correlated components (0.69) and the third in direct effect (0.16), this may be due to the indirect effect of number of spikes/m 2 and 1000 grain weight via number of grain/spike, 0.19 and 0.35, respectively which was more than the indirect effect of number of grain/spike and 1000 grain weight via number of spikes/m 2 , 0.09 and 0.14, respectively, where the more the indirect effect the less direct effect. The results of correlation and direct effect of number of spikes/m 2 and 1000 grain weight are agreed with those obtained from [19]. …”
Section: Path Analysis and Correlation Between Grain Yield And Yield supporting
confidence: 87%
“…The results of correlation and path analysis are matching for 1000 grain weight, however, the reverse was the case for the other two components where number of grain/spike was the second correlated components (0.69) and the third in direct effect (0.16), this may be due to the indirect effect of number of spikes/m 2 and 1000 grain weight via number of grain/spike, 0.19 and 0.35, respectively which was more than the indirect effect of number of grain/spike and 1000 grain weight via number of spikes/m 2 , 0.09 and 0.14, respectively, where the more the indirect effect the less direct effect. The results of correlation and direct effect of number of spikes/m 2 and 1000 grain weight are agreed with those obtained from [19]. …”
Section: Path Analysis and Correlation Between Grain Yield And Yield supporting
confidence: 87%
“…A esse respeito, Okuyama et al (2004) afirmaram que o estudo mais detalhado das relações, obtidas pela análise de trilha, mostrou que a relação entre rendimento de grãos e seus componentes é bastante diferente das apresentadas pela análise de correlação simples. A aparente divergência ocorre em razão da abordagem analítica.…”
Section: Resultsunclassified
“…In a previous paper (OKUYAMA et al, 2004) was reported that the number of spikes m -2 and the number of grains per spike, followed by the above-ground biomass.m -2 should be taken into account to enhance wheat grain yield. This paper provides evidence that some plant traits may be used to complement selection based on yield components in wheat.…”
Section: Resultsmentioning
confidence: 99%
“…OKUYAMA et al (2004). In each subplot, a sample of one row with 1m in length was used to randomly selected 10 main tillers for the following determinations: flag leaf length (distance from base to tip of the flag leaf blade), p e d u n c l e e x t r u s i o n l e n g t h ( d i s t a n c e f r o m insertion of flag leaf blade to basal node of spike), peduncle length (distance from upper node to the basal node of spike), spike length (distance from the base to the end of spike), sheath length (difference of peduncle length and peduncle extrusion length) and plant height (distance from the ground to the tip of the spike).…”
Section: Methodsmentioning
confidence: 99%